Central nervous system, spinal root ganglion and brachial plexus involvement in leprosy: A prospective study. (13th October 2022) - Verma, Sumit; Garg, Ravindra Kumar; Rizvi, Imran; Malhotra, Hardeep Singh; Kumar, Neeraj; Jain, Amita; Suvirya, Swastika; Parihar, Anit; Verma, Rajesh; Sharma, Praveen Kumar; Pandey, Shweta; Uniyal, Ravi; et al.
Background: Leprosy is primarily a disease of peripheral nerves. Some isolated case reports and case series have communicated imaging changes in the central nervous system (CNS) and brachial plexus in patients with leprosy. Objectives: To study the neuroimaging abnormalities in patients with lepra bacilli-positive neuropathy in the context of CNS, spinal root ganglion, and brachial plexus. Design: Prospective observational study Methods: We screened newly-diagnosed patients with multibacillary leprosy presenting with neuropathy. Patients with bacilli-positive sural nerve biopsies were included in the study and subjected to magnetic resonance imaging (MRI) of the brain and spinal cord. Results: A total of 54 patients with bacteriologically confirmed multibacillary leprosy were screened; Mycobacterium leprae was demonstrated in the sural nerve biopsies of 29 patients. Five patients (5/29; 17.24%) had MRI abnormalities in CNS, spinal root ganglion, and/or brachial plexus. Three patients had MRI changes suggestive of either myelitis or ganglionitis. One patient had T2/FLAIR hyperintensity in the middle cerebellar peduncle while 1 had T2/FLAIR hyperintensity in the brachial plexus. Conclusion: CNS, spinal root ganglion, and brachial plexus are involved in patients with leprous neuropathy. Immunological reaction against M leprae antigen might be a plausible pathogenetic mechanism for brachial plexus and CNS imaging abnormalities.